Exploring the cognitive and motivational drivers of women’s sustainable entrepreneurial intention - Imam Suwandi; Mohammad Benny Alexandri; Agus Taryana; Arif Zainudin (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2025)
This study investigates the psychological factors that shape sustainable entrepreneurial intention among women entrepreneurs affiliated with the Indonesian Women Entrepreneurs Association (IWAPI), a prominent national organization that empowers female business actors. The research explores the influence of entrepreneurial mindset, entrepreneurial motivation, and entrepreneurial self-efficacy using a quantitative approach with partial least squares structural equation modeling on survey data collected from members in Banten Province. The findings reveal that entrepreneurial mindset significantly enhances both entrepreneurial motivation and entrepreneurial self-efficacy, while entrepreneurial self-efficacy emerges as the strongest direct predictor of sustainable entrepreneurial intention. Further analysis confirms that entrepreneurial mindset also affects intention indirectly through motivational and efficacy pathways. Moreover, the multi-group analysis indicates that age moderates the relationship between entrepreneurial self-efficacy and sustainable entrepreneurial intention, with stronger effects observed among older respondents. These results highlight the layered psychological mechanisms that support sustainable entrepreneurship and underscore the strategic role of organizations such as the Indonesian Women Entrepreneurs Association in nurturing entrepreneurial capacity. The study contributes to the literature on entrepreneurial psychology and provides practical implications for age-sensitive policies and empowerment programs that support women-led sustainable business development